An Evaluation of Scholarly Works of Tax Incentives in Indonesia : Bibliometric Analysis of Policy Learning - Ririn Riani; Aam Slamet Rusydiana (Accounting and Sustainability, 2022)
Over the years, the issue of tax policy design has been a major concern requiring extensive scientific research. In light of these considerations, the purpose of this paper is to investigate the extent to which prior research has focused on tax incentives in Indonesia. This paper employs bibliometric analytic techniques to examine the empirical literature published between 1987 and 2023. This paper utilizes the Scopus database and the "bibliometrix" package to conduct a bibliometric analysis. The analysis emphasizes on the most important information regarding the analysis of scientific production by field (journals, authors, and keywords), mapping the research path and proposing initiatives based on prior literature. This investigation revealed various results. Initially, the government must offer 'renewable' and 'sustainable' tax incentives to vital businesses and economic sectors. Second, tax incentives should also be provided to the MSMEs industry, as this industry has the largest market as a pillar of Indonesia's economy. There is a great deal of room for theoretical development, contextualization, and methodological contributions. In addition, this study provides policy recommendations from prior research and directions for future research.